Technology on snow and ice: Innovation, monitoring, and performance for the Olympic Winter Games Milano Cortina 2026 - Almqvist, A.; Supej, M.; Düking, P.; Stöggl, T.; Holmberg, H.-C. (Scandinavian Journal of Medicine & Science in Sports, 2026)
Elite performance in Olympic winter sports depends on the interplay among the athlete, equipment, and the snow or ice. This naturally evolves with temperature, humidity, wind, preparation, and contact between the equipment and its surface. Together, these factors continuously rebalance the forces of gravity, aerodynamic drag, and friction, requiring athletes, coaches, and organizers to adapt technique, equipment, and surface management, e.g., snow grooming and salting, ice resurfacing or pebbling, and rink climate control. This narrative review (SANRA-guided) synthesizes the scientific literature across four domains: (i) the evolution of equipment and athlete-surface interaction; (ii) the physics of resistive forces and targeted countermeasures; (iii) sensing and monitoring with robust, field-validated technologies and analytics; and (iv) the digitalization of coaching, officiating, and broadcasting. We integrate design and validation with sport regulations and governance. This includes the ban on fluorinated waxes, geometry and mass limits, and principles for data stewardship, model transparency, and fairness. A central component of this review is the assessment of quality aspects of technologies, including the assessment of ecological validity under field-specific conditions before their use in high-stakes coaching, medical, or officiating decisions. We conclude with actionable recommendations for Milano-Cortina 2026: (i) align equipment and surface preparation with expected regimes of drag and friction; (ii) deploy sensors and analytics with demonstrated accuracy, precision, and reliability; (iii) quantify uncertainty in key performance indicators; and (iv) treat federation rules as a priori design constraints. This approach enables innovation to deliver faster, safer, and more equitable outcomes in winter sport at Milano-Cortina 2026 and beyond.